2009
DOI: 10.1007/s00221-009-2011-2
|View full text |Cite
|
Sign up to set email alerts
|

Control of dynamic stability during adaptation to gait termination on a slippery surface

Abstract: An unexpected slip during gait termination results in a generalised slip response designed to regain stability and prevent a fall. With knowledge of and experience with a slippery surface, locomotor behaviour adapts to proactively diminish the effect of the slip and improve the reactive control during the slip. Our purpose was to examine the organisation of the adaptation to a slippery surface during gait termination. After receiving an unexpected slip during gait termination, participants (N = 8) experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…A flatter foot is a proactive movement in anticipation of a slippery surface 11, 1317 that reduces shear contact forces. The control group used this strategy to reduce the effect of the slip perturbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A flatter foot is a proactive movement in anticipation of a slippery surface 11, 1317 that reduces shear contact forces. The control group used this strategy to reduce the effect of the slip perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…Feedforward adaptations include shorter steps onto the slippery surface 1116 , an increased stability margin 11, 17 , a forward centre of mass (COM) shift 11, 1820 and a decreased foot-floor angle to reduce shear contact forces 1114, 16, 17, 20 . Adaptations to feedback-based responses include increases in the subsequent step length 17, 19, 21, 22 and a more stable COM-base of support (BOS) relationship 12, 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The risk of experiencing a slip (Chambers and Cham, 2007;Lockhart and Kim, 2006;Oates et al, 2010) or trip (Austin et al, 1999) accident is influenced by the shoeesurface interface, particularly at the time of initial contact with the ground and during the pre-swing of the gait cycle. When walking on a level, even surface while wearing everyday footwear, healthy individuals usually make the necessary adjustments to maintain balance in order to avoid a slip or trip (Austin et al, 1999;Chambers and Cham, 2007;Tang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It should also be mentioned that the older adults in this study had a significantly higher mass than the young adults, although the effect of increased mass on slip adaptations after slip exposure, if any, is unknown, although Wu et al (2013) found no significant differences in resultant RCOF during walking without slip exposure between obese and non-obese. Previous research has concluded that laboratory subjects should be limited to a single slip if real-world slips are desired due to gait adaptations noted after slipping Oates et al, 2010). However, the ability to generate more than one unexpected slip in a laboratory environment will likely depend on the population of interest.…”
mentioning
confidence: 94%